Primary tuberculous osteomyelitis of the mandible: A rare case report - J Kannaperuman; Gowri Natarajarathinam; Anusha V Rao; Sudha Palanimuthu (Wolters Kluwer Medknow Publications, 2013)
Tuberculosis (TB) has become a rare disease in the developed countries but it is still a serious problem in developing countries. Incidence of tuberculous osteomyelitis of the jaw bones is very low. This rare incidence is the primary reason that this lesion gets mis-diagnosed many times. Here we report the diagnosis, treatment and follow-up of a case, which is a classical presentation of tuberculous osteomyelitis of mandible. Primary tuberculous osteomyelitis is a very rare entity but in the recent times, increased incidence of TB as a coinfection of HIV, has posed a big challenge in developing countries. If not diagnosed, at the right time, this can lead to serious complications like internal organ damage, tuberculous meningitis etc., Early diagnosis of tuberculous osteomyelitis will certainly reduce the morbidity of this disease condition.